Theory and practice in Essene law - Amihay, Aryeh 1977- (New York, NY Oxford University Press, 2017)
"Presenting a novel approach for the study of law in the Dead Sea scrolls, this book is conveniently divided into concepts and practices, highlighting the discrepancies between the two. A valuable study for anyone interested in Jewish law, legal history, sectarianism and communal life"--
Part I. Concepts. 1. Legal essentialism -- 2. Hierarchy and exclusivity -- 3. Time and space -- 4. Obligation and authority -- 5. Intent and responsibility -- 6. Retribution and control -- Part II. Practices. shifting from theory to practice -- 7. Association and admission -- 8. Covenant and initiation -- 9. Officers and leaders -- 10. Reproof and mediation -- 11. Punishment and exclusion
Keywords: Essenes; Jewish Law -- History